Pathogenesis of congenital hepatic fibrosis and current status of its diagnosis and treatment - FENG Maosen (Linchuang Gandanbing Zazhi, 2017)
Congenital hepatic fibrosis (CHF) is a rare disease commonly seen in children and might be caused by ductal plate malformation associated with congenital gene defect. So far, the pathogenesis of this disease remains unclear, and present studies have reported that polycystic kidney and hepatic disease 1 gene mutation may be one of the most important reasons for the development of CHF. Patients are mainly manifested as portal hypertension and recurrent cholangitis, often complicated by renal diseases. The therapeutic principle mainly focuses on controlling portal hypertension and related complications and slowing down the progression of CHF. Timely treatment helps patients to achieve a relatively good prognosis. However, there are still no effective therapies for ductal plate malformation. This article reviews the pathogenesis and current status of treatment of CHF in China and foreign countries to provide a reference for the diagnosis and treatment of CHF.